A Taxonomic Study of Family Hemiramphidae from Indian Waters - Anwesha Behera; Jeevan T. M; A. Pavan Kumar; A. K. Jaiswar (Journal of Indian Fisheries Association, 2023)
The order Beloniformes consists of minor pelagic fish species that are considered valuable resources and can be found in marine, brackish, and freshwater habitats. In India, although they do not contribute significantly to commercial fish landings, they play a remarkable role in the pelagic fishery of Tamil Nadu state, accounting for approximately 42.6% of the total beloniform catch in the country. During this study, taxonomic analysis was conducted based on morpho-meristic characteristics, otolith morphology, and DNA techniques. The results confirmed the existence of six distinct species including Hemiramphus far, Hemiramphus lutkei, Hemiramphus archipelagicus, Hyporhamphus limbatus, Rhynchorhamhus naga and Rhynchorhamphus georgii belonging to family Hemiramphidae, in Indian waters. In addition, DNA barcodes were generated for all the aforementioned species. These genetic sequences have been deposited in the Gene Bank, specifically in the BOLD Systems database. Notably, the study has generated barcodes by using COI gene for Hemiramphus archipelagicus and Hemiramphus lutkei for the first time.